Binder, binder slurry, preparation method of binder slurry, current collector prime coat slurry and negative plate
By using a new adhesive with core-shell structure, the problems of uneven dispersion, poor coating fluidity and insufficient peeling force of the lithium-ion battery negative electrode primer are solved, and better battery performance and reliability are achieved.
Patent Information
- Application Number
- CN202411424515.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing lithium-ion battery negative electrode primer slurry has problems such as uneven dispersion, poor coating fluidity and insufficient peeling force.
New adhesives with core-shell structures, including inner core layer, intermediate layer and outer shell layer, are used to improve the strength and dispersion of the adhesive by precisely controlling the molar ratio and polymerization structure of the comonomer.
The slurry dispersion, coating fluidity and peel strength of the negative electrode basecoat are significantly improved, and the overall performance and reliability of the battery are improved.
Smart Images

Figure CN119463756A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a binder, a binder slurry, a method for preparing the binder slurry, a current collector primer slurry and a negative electrode sheet. Background Art
[0002] At present, in the lithium-ion battery 3C system industry, the negative electrode introduces a copper foil primer to improve the stripping force and contact impedance. Usually, the negative electrode primer formula is a conductive agent (CNT / SP / graphene, etc.) + CMC + SBR system, and a small amount of dispersant is added to improve the dispersion of CNT / SP, and a certain leveling agent is added to improve the wetting and leveling of the thinly coated conductive agent on the copper foil surface. At present, the negative electrode primer formula has problems such as uneven dispersion of the primer slurry, poor fluidity of gravure coating, particle pits in the coating, and insufficient stripping force after coating.
[0003] At present, the emulsion stability of conventional SBR is average, and its ability to disperse and stabilize SP and CNT in the slurry is insufficient, which easily leads to problems such as particles and insufficient peeling force after primer coating. Secondly, the existing dispersants have a small molecular weight. The small molecules of alcohol ether dispersants enter the electrolyte after the battery cell is injected and are easily oxidized at the positive electrode, thereby deteriorating electrical properties such as gas production.
[0004] Therefore, designing and developing a new type of SBR and its formulation is crucial to solving the problems existing in the existing negative electrode primer formulation. Summary of the invention
[0005] Aiming at the problems of uneven dispersion, poor coating fluidity and insufficient peeling strength of negative electrode primer slurry in the prior art, a binder, a binder slurry, a method for preparing the binder slurry, a current collector primer slurry and a negative electrode sheet are provided.
[0006] In one aspect, the present invention provides a binder, wherein the binder is a core-shell structure, comprising an inner core layer, an intermediate layer and an outer shell layer, wherein the intermediate layer is disposed between the inner core layer and the outer shell layer, and the comonomer of the inner core layer comprises an olefin monomer, an aromatic vinyl monomer and an unsaturated amide monomer; The comonomers of the intermediate layer include olefin monomers, aromatic vinyl monomers and unsaturated ester monomers; The comonomers of the outer shell layer include olefin monomers, sulfonic acid monomers, alcohol ether monomers and acrylic acid monomers.
[0007] Optionally, the molar ratio of the comonomers of the inner core layer, the middle layer and the outer shell layer is (20-30): (40-60): (10-40).
[0008] Optionally, the molar ratio of olefin monomers, aromatic vinyl monomers and unsaturated amide monomers in the inner core layer is (10-30): (64-84): (5-7).
[0009] Optionally, the molar ratio of the olefin monomer, the aromatic vinyl monomer and the unsaturated ester monomer in the intermediate layer is (30-40): (40-50): (10-30).
[0010] Optionally, the molar ratio of olefin monomers, sulfonic acid monomers, alcohol ether monomers and acrylic acid monomers in the outer shell layer is (30-40): (10-20): (20-30): (20-30).
[0011] Optionally, the aggregation structure of the kernel layer is: , Wherein, x is the degree of polymerization of the olefin monomer, y is the degree of polymerization of the aromatic vinyl monomer, and z is the degree of polymerization of the unsaturated amide monomer, x:y:z = (10-30): (64-84): (5-7).
[0012] Optionally, the polymerization structure of the middle layer is: , Wherein, m is the degree of polymerization of the olefin monomer, n is the degree of polymerization of the aromatic vinyl monomer, and p is the degree of polymerization of the unsaturated ester monomer, m:n:p = (30-40): (40-50): (10-30).
[0013] Optionally, the polymer structure of the outer shell layer is: , Among them, a is the degree of polymerization of olefin monomers, b is the degree of polymerization of sulfonic acid monomers, c is the degree of polymerization of alcohol ether monomers, and d is the degree of polymerization of acrylic acid monomers, a:b:c:d=(30-40):(10-20):(20-30):(20-30).
[0014] Optionally, the olefin monomers include one or more of butadiene and isoprene; the aromatic vinyl monomers include one or more of styrene, α-methylstyrene, and vinyltoluene; the unsaturated amide monomers include one or more of acrylamide, 2-acrylamide, methacrylamide, dimethylaminopropyl acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid; and / or the unsaturated ester monomers include one or more of methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methoxyethyl acrylate, and pentaerythritol triacrylate; and / or, the sulfonic acid monomer includes one or more of 2-acrylamide-2-methylpropanesulfonic acid, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 2-(styrenesulfonyl)acetic acid, and allyl methylthiosulfonate; and / or, the alcohol ether monomer includes one or more of trihydroxy polyoxypropylene ether, allyl phenyl ether, 2-methyl-3-phenyl-2-propene-1-ol, and 1-(furan-2-yl)but-3-ene-1-ol; and / or, the acrylic acid monomer includes one or more of acrylic acid, maleic acid, and itaconic acid.
[0015] On the other hand, the present invention provides a binder slurry, comprising a first solvent and the binder, wherein the solid content of the binder slurry is 35%-40%.
[0016] Optionally, the binder slurry further includes an emulsifier, an initiator and a terminator; Taking the total mass of the binder slurry as 100%, the mass percentage of the emulsifier is 1%-2%, the mass percentage of the initiator is 0.4%-0.6%, and the mass percentage of the terminator is 1%-2%.
[0017] Optionally, the emulsifier includes one or more of alkyl sulfonates - sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate, sodium dodecylbenzene sulfonate; and / or The initiator is a redox initiator, and the redox initiator includes one or more of dicumyl peroxide, azobisisobutyronitrile and ferrous sulfate; and / or The stopper includes one or more of 2-mercaptoethanol, 3-mercaptopropionic acid, 4-mercaptobutyric acid and 6-mercaptohexanoic acid.
[0018] Optional, including the following operations: S1: taking the comonomer of the inner core layer and adding it into the emulsion, mixing it evenly, and obtaining the inner core layer glue after polymerization reaction; S2: taking the comonomer of the middle layer and adding it into the inner core layer glue solution, mixing them evenly, and obtaining the inner core layer-middle layer glue solution after polymerization reaction; S3: Take the comonomer of the outer shell layer and add it into the inner core layer-middle layer glue solution, mix well, and obtain the adhesive slurry after polymerization reaction.
[0019] Optionally, the particle size D50 of the particles in the inner core layer glue is greater than 100 nm, and the viscosity of the inner core layer glue is greater than 100 cps; The particle size D50 of the inner core layer-middle layer glue solution is greater than 350 nm, and the viscosity of the inner core layer-middle layer glue solution is greater than 300 cps; The particle size D50 of the binder is less than 500 nm, and the viscosity of the binder slurry is greater than or equal to 600 cps.
[0020] Optionally, the reaction temperature for preparing the inner core layer glue is 20-40° C., the reaction time is 3-8 h, and the reaction pressure is 5-8 MPa; The reaction temperature for preparing the inner core layer-intermediate layer glue solution is 30-50°C, the reaction time is 8-10h, and the reaction pressure is 3-7Mpa; The reaction temperature for preparing the core-shell structure binder is 20-40° C., the reaction time is 5-8 hours, and the reaction pressure is 3-5 MPa.
[0021] In another aspect, the present invention provides a current collector primer slurry, comprising a second solvent, a conductive agent and the binder according to claim 1.
[0022] Optionally, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and carbon fibers; Taking the total mass of the current collector primer slurry as 100%, the mass percentage of the conductive agent is 50%-70%, and the mass percentage of the binder is 30%-50%.
[0023] In another aspect, the present invention provides a negative electrode sheet, comprising a current collector, an undercoat layer and a negative electrode active material layer, wherein the undercoat layer is located between the current collector and the negative electrode active material layer; The primer layer includes the binder, or the primer layer is obtained by coating and curing the current collector primer slurry as claimed in claim 1.
[0024] The beneficial effects of the present invention are: The adhesive provided by the present application includes an inner core layer, an intermediate layer and an outer shell layer, and the inner core layer, the intermediate layer and the outer shell layer together constitute an adhesive having a core-shell structure, wherein the inner core layer includes an aromatic vinyl monomer having a high glass transition temperature and is cross-linked with an unsaturated amide monomer, thereby improving the strength of the inner core layer, thereby facilitating the improvement of the overall structural strength of the adhesive after coating, and at the same time, the adhesive is not prone to collapse during the baking operation after coating, thereby ensuring the particle dispersion and adhesion of the adhesive; In addition, the middle layer of the binder includes olefin monomers and unsaturated ester monomers with low glass transition temperature. Compared with the inner core layer, the middle layer has low strength. After coating, it can ensure the electrolyte infiltration and adhesion of the main material particles and the foil material, which is conducive to the generation of a bonding interface and a dispersion force interface, ensuring the bonding and dispersion of the binder particles, and improving the peel strength of the binder. The outer shell layer of the binder provides charge stabilization and steric hindrance effects for the binder through the sulfonic acid groups in the sulfonic acid monomers and the carboxylic acid functional groups in the acrylic monomers, thereby ensuring the uniform dispersion of the binder particles. In addition, the outer shell layer also contains ether alcohol monomers to reduce the surface tension of the particles in the binder, making it easier for the particles to wet the conductive agent particles and form hydrogen bonding forces, thereby achieving a high dispersion effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the core-shell structure of the binder provided by the present invention. DETAILED DESCRIPTION
[0026] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] Reference Figure 1 The present invention provides a binder, which has a core-shell structure, including a core layer, an intermediate layer and an outer shell layer, wherein the intermediate layer is arranged between the core layer and the outer shell layer, and the comonomer of the core layer includes an olefin monomer, an aromatic vinyl monomer and an unsaturated amide monomer; The comonomers of the intermediate layer include olefin monomers, aromatic vinyl monomers and unsaturated ester monomers; The comonomers of the outer shell layer include olefin monomers, sulfonic acid monomers, alcohol ether monomers and acrylic acid monomers.
[0028] Specifically, the binder provided by the present application includes a core layer, an intermediate layer and an outer shell layer, and the core layer, the intermediate layer and the outer shell layer together constitute a binder with a core-shell structure, wherein the core layer is a hard core structure and includes an olefin monomer with a high glass transition temperature, which is beneficial for the SBR core structure to be relatively hard, and is convenient for the SBR to maintain a spherical structure after coating and baking, and is not easy to collapse, which is beneficial for lithium ion conduction, reduces DCR, and improves the strength of the core layer, thereby facilitating the improvement of the overall structural strength of the binder after coating, and at the same time, it is not easy to collapse during the baking operation after coating, thereby ensuring the particle dispersion and adhesion of the binder; In addition, the middle layer of the adhesive adopts a soft shell structure and uses a monomer with a low Tg temperature. Compared with the inner core layer, the middle layer has a lower strength. After coating, it can ensure the electrolyte infiltration and adhesion of the main material particles and the foil material, which is conducive to the generation of a bonding interface and a dispersion force interface, ensuring the bonding and dispersion of the adhesive particles, and at the same time improving the peel strength of the adhesive. The outer shell layer of the binder adopts a sulfonic acid and alcohol ether structure. The sulfonic acid group in the sulfonic acid monomer and the carboxylic acid functional group in the acrylic monomer provide the binder with charge stability and steric hindrance effects, thereby ensuring the uniformity of the dispersion of the binder particles. In addition, ether alcohol monomers are added to the outer shell layer to reduce the surface tension of the particles in the binder, making it easier for the particles to wet the conductive agent particles, thereby achieving a high dispersion effect.
[0029] The inner core layer is a hard core structure. By using monomers with high glass transition temperature and cross-linking structure, the inner core structure of the binder is relatively hard, which is convenient for the binder to maintain a spherical structure after coating and baking, and is not easy to collapse, which is conducive to lithium ion conduction and reduces DCR. The middle layer adopts a soft shell structure and uses a monomer with a low glass transition temperature, which makes the adhesive middle layer softer, making it easier for it to adhere to the foil and the conductive agent to form a bonding interface, which is beneficial to increase the bonding area; The outer shell layer adopts sulfonic acid and alcohol ether structure, which is beneficial to provide outer layer charge, improve the dispersion effect of the binder, and improve the dispersion of the conductive agent in the slurry; thereby improving the conductive performance and reducing DCR; at the same time, it can broaden the bonding interface and bonding force of the binder, thereby improving the peeling force; In some embodiments, the molar ratio of the comonomers of the inner core layer, the middle layer, and the outer shell layer is (20-30): (40-60): (10-40).
[0030] Specifically, the molar ratio of the monomers of the inner core layer, the middle layer and the outer shell layer includes but is not limited to 30:60:10, 30:50:20 or 30:40:30, as long as the molar ratio of the monomers of the inner core layer, the middle layer and the outer shell layer in the present application is within the range of (20-30): (40-60): (10-40).
[0031] In some embodiments, the molar ratio of the olefin monomer, the aromatic vinyl monomer, and the unsaturated amide monomer in the inner core layer is (10-30): (64-84): (5-7).
[0032] Specifically, among the mass proportions of olefin monomers, aromatic vinyl monomers and unsaturated amide monomers in the inner core layer, the proportion of aromatic vinyl monomers is relatively high. This setting is beneficial to improving the strength of the inner core layer, and further to improving the overall structural strength after the adhesive is coated; specifically, the molar ratio of olefin monomers, aromatic vinyl monomers and unsaturated amide monomers in the inner core layer can be 10:84:6, 20:74:6, 25:68:7 or 30:65:5, satisfying that the molar ratio of olefin monomers, aromatic vinyl monomers and unsaturated amide monomers in the inner core layer is (10-30): (64-84): (5-7).
[0033] In some embodiments, the molar ratio of the olefin monomer, the aromatic vinyl monomer, and the unsaturated ester monomer in the intermediate layer is (30-40): (40-50): (10-30).
[0034] Specifically, when the molar ratio of the olefin monomer, aromatic vinyl monomer and unsaturated ester monomer in the intermediate layer is (30-40): (40-50): (10-30), the electrolyte can be ensured to infiltrate and adhere to the main material particles and the foil after coating, which is conducive to the generation of a bonding interface and a dispersion force interface, ensuring the bonding and dispersion of the adhesive particles, and at the same time improving the peel strength of the adhesive.
[0035] In some embodiments, the molar ratio of the olefin monomer, the sulfonic acid monomer, the alcohol ether monomer and the acrylic acid monomer in the outer shell layer is (30-40): (10-20): (20-30): (20-30).
[0036] Specifically, when the molar ratio of olefin monomers, sulfonic acid monomers, alcohol ether monomers and acrylic acid monomers in the outer shell layer is (30-40): (10-20): (20-30): (20-30), the sulfonic acid groups in the sulfonic acid monomers and the carboxylic acid functional groups in the acrylic acid monomers provide charge stabilization and steric hindrance effects for the binder, thereby ensuring the uniformity of the dispersion of the binder particles. In addition, the outer shell layer also contains ether alcohol monomers to reduce the surface tension of the particles in the binder, making it easier for the particles to wet the conductive agent particles and form hydrogen bonding forces, thereby achieving a high dispersion effect.
[0037] In some embodiments, the aggregation structure of the inner core layer is: , Wherein, x is the degree of polymerization of the olefin monomer, y is the degree of polymerization of the aromatic vinyl monomer, and z is the degree of polymerization of the unsaturated amide monomer, x:y:z = (10-30): (64-84): (5-7).
[0038] Specifically, in the polymerization structure of the inner core layer, the degree of polymerization of the aromatic vinyl monomer in the copolymer is relatively high, and the degree of polymerization of the olefin monomer and the unsaturated amide monomer is relatively low. The relatively high degree of polymerization of the aromatic vinyl monomer is conducive to improving the overall strength of the inner core layer and improving the peel strength between the coating and the substrate; that is, by adjusting the degree of polymerization of different monomers to adjust the proportion of each monomer, the structure of the polymer is optimized, and the dispersibility of the slurry is improved. The addition of olefin monomers and unsaturated amide monomers may help break the close stacking between the aromatic vinyl monomers and promote better dispersion; In summary, by precisely controlling the degree of polymerization ratio of olefin monomers, aromatic vinyl monomers and unsaturated amide monomers, the slurry dispersibility, coating fluidity and peel strength of the negative electrode undercoat layer can be significantly improved, thereby improving the overall performance and reliability of the battery.
[0039] In some embodiments, the polymeric structure of the intermediate layer is: , Wherein, m is the degree of polymerization of the olefin monomer, n is the degree of polymerization of the aromatic vinyl monomer, and p is the degree of polymerization of the unsaturated ester monomer, m:n:p = (30-40): (40-50): (10-30).
[0040] Specifically, in the polymerization structure of the intermediate layer, by adjusting the ratio of the polymerization degree of olefin monomers, the polymerization degree of aromatic vinyl monomers and the polymerization degree of unsaturated ester monomers, the structure of the polymer chain is optimized to make it more evenly distributed, reduce the aggregation phenomenon between particles, and thus significantly improve the dispersibility of the slurry; the polar functional groups introduced by the unsaturated ester monomers can increase the hydrophilicity of the polymer, help to disperse the slurry in water and ensure the electrolyte infiltration after coating; by reasonably controlling the ratio of olefin monomers and aromatic vinyl monomers, the surface tension of the polymer can be reduced, further promoting the uniform dispersion of the slurry.
[0041] In some embodiments, the polymeric structure of the outer shell layer is: , Among them, a is the degree of polymerization of olefin monomers, b is the degree of polymerization of sulfonic acid monomers, c is the degree of polymerization of alcohol ether monomers, and d is the degree of polymerization of acrylic acid monomers, a:b:c:d=(30-40):(10-20):(20-30):(20-30).
[0042] The addition of sulfonic acid monomers and acrylic monomers can increase the flexibility of the polymer chain, making the coating easier to flow and spread during the coating process; the appropriate content of alcohol ether monomers can improve the thermal stability of the polymer, prevent decomposition or deformation during high-temperature coating, and maintain coating fluidity; sulfonic acid monomers and acrylic monomers can increase the cross-linking density of the polymer, forming a denser network structure, and further improving the peel strength.
[0043] By adjusting the polymerization degree of olefin monomers, sulfonic acid monomers, and the polymerization degree ratio of alcohol ether monomers and acrylic monomers, the molecular weight distribution of the polymer is controlled to make it more in line with the requirements of the coating process, thereby improving the coating fluidity.
[0044] In some embodiments, the olefin monomer includes one or more of butadiene and isoprene; In some embodiments, the aromatic vinyl monomer includes one or more of styrene, α-methylstyrene, and vinyltoluene; In some embodiments, the unsaturated amide monomers include one or more of acrylamide, 2-acrylamide, methacrylamide, dimethylaminopropyl acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid; In some embodiments, the unsaturated ester monomer includes one or more of methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methoxyethyl acrylate, and pentaerythritol triacrylate; In some embodiments, the sulfonic acid monomer includes one or more of 2-acrylamide-2-methylpropanesulfonic acid, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 2-(styrenesulfonyl)acetic acid, and allyl methylthiosulfonate; In some embodiments, the alcohol ether monomer includes one or more of trihydroxy polyoxypropylene ether, propenyl phenyl ether, 2-methyl-3-phenyl-2-propene-1-ol, and 1-(furan-2-yl)but-3-en-1-ol; In some embodiments, the acrylic monomer includes one or more of acrylic acid, maleic acid, and itaconic acid.
[0045] Specifically, in the embodiments provided in the present application, the olefin monomer is selected from butadiene, the aromatic vinyl monomer is selected from styrene, the unsaturated amide monomer is selected from one or more of acrylamide, 2-acrylamide, and dimethylaminopropyl acrylamide; the unsaturated ester monomer is selected from one or more of ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate and pentaerythritol triacrylate; the sulfonic acid monomer is selected from one or more of 2-acrylamide-2-methylpropanesulfonic acid and 2-(styrenesulfonic)acetic acid; the alcohol ether monomer is selected from one or more of trihydroxy polyoxypropylene ether, propenyl phenyl ether, and 2-methyl-3-phenyl-2-propene-1-ol; the acrylic acid monomer is selected from one or more of maleic acid and itaconic acid.
[0046] In another embodiment of the present invention, there is provided a binder slurry, comprising a first solvent and the binder, wherein the solid content of the binder in the binder slurry is 35%-40%.
[0047] Specifically, the solid content of the binder in the binder slurry can be 35%, 37%, 38% or 40%; the solid content within the range of 35%-40% can ensure that the binder slurry has good stability, which is beneficial to the coating and drying process of the processing. In addition, the appropriate solid content in the binder slurry can reduce the sedimentation of particles in the slurry, maintain the uniformity of the slurry, and thus improve the quality of the electrode.
[0048] In some embodiments, the binder further comprises an emulsifier, an initiator, and a terminating agent; Taking the total mass of the binder slurry as 100%, the mass percentage of the emulsifier is 1%-2%, the mass percentage of the initiator is 0.4%-0.6%, and the mass percentage of the terminator is 1%-2%.
[0049] The mass proportion of the emulsifier can be 1%, 2% or 3%. In a specific embodiment, the mass proportion of the emulsifier is 2%. In some embodiments, the emulsifier includes one or more of alkyl sulfonates-sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate, sodium dodecylbenzene sulfonate and potassium disproportionated rosin soap; and / or The initiator is a redox initiator, and the redox initiator includes one or more of dicumyl peroxide, azobisisobutyronitrile and ferrous sulfate; and / or The stopper includes one or more of 2-mercaptoethanol, 3-mercaptopropionic acid, 4-mercaptobutyric acid and 6-mercaptohexanoic acid.
[0050] Specifically, in a preferred embodiment, the emulsifier is selected from at least one of sodium dodecylbenzene sulfonate and disproportionated rosin acid potassium soap.
[0051] In another embodiment, the present invention provides a method for preparing a binder slurry, comprising the following operations: S1: taking the comonomer of the inner core layer and adding it into the emulsion, mixing it evenly, and obtaining the inner core layer glue after polymerization reaction; S2: taking the comonomer of the middle layer and adding it into the inner core layer glue solution, mixing them evenly, and obtaining the inner core layer-middle layer glue solution after polymerization reaction; S3: Take the comonomer of the outer shell layer and add it into the inner core layer-middle layer glue solution, mix well, and obtain the adhesive slurry after polymerization reaction.
[0052] In the method for preparing the binder slurry, the specific operations include: First, add deionized water to a 50L high-pressure reactor, accounting for about 40-60% of the volume of the reactor, then add the emulsifier, stir thoroughly at 5-8m / s, add the electrolyte, and stir thoroughly to disperse evenly.
[0053] The inner core layer comonomers are added into the reactor in a molar ratio of butadiene:styrene:acrylamide = (10-30): (64-84): (5-7), fully stirred and dispersed evenly, the pressure in the reactor is adjusted to 5-8Mpa, the temperature in the reactor is adjusted to 20-40°C, and then an initiator is added to promote the copolymerization reaction of the inner core layer comonomers. The reaction is carried out for 3-8 hours to obtain the inner core layer glue.
[0054] The inner core layer glue solution is transferred to an 80L high-pressure reactor, and a certain amount of emulsifier, deionized water and electrolyte are added. Then, the middle layer copolymer monomer is added according to the molar ratio of styrene: butadiene: acrylate = (30-40): (40-50): (10-30), and the mixture is fully stirred and dispersed evenly. The temperature in the reactor is adjusted to 30-50°C and the pressure in the reactor is adjusted to 3-7Mpa. A redox initiator is added, and then the mixture is fully stirred at a linear speed of 8m / s. After reacting for 8-10h, when the conversion rate reaches 70-80%, the inner core layer-middle layer glue solution is obtained.
[0055] On the basis of the above inner core layer-middle layer glue, continue to add a certain amount of emulsifier, deionized water, etc., and then stir it evenly at a linear speed of 5 m / s, and then add the outer shell layer copolymer monomer with a molar ratio of butadiene: sulfonic acid: alcohol ether: acrylic acid = (30-40): (10-20): (20-30): (20-30), add the initiator under 20-40°C environment and 3-5Mpa conditions, react for 5-8h, and when the conversion rate reaches 85-95%, a core-shell structure adhesive is obtained.
[0056] In some embodiments, the particle size D50 of the particles in the inner core layer glue is greater than 100 nm, and the viscosity of the inner core layer glue is greater than 100 cps; The particle size D50 of the inner core layer-middle layer glue solution is greater than 350 nm, and the viscosity of the inner core layer-middle layer glue solution is greater than 300 cps; The particle size D50 of the core-shell structured binder particles is less than 500 nm, and the viscosity of the core-shell structured binder is greater than or equal to 600 cps.
[0057] Specifically, the particle size D50 of the particles in the inner core layer glue is 120 nm, and the viscosity of the inner core layer glue is 300 cps; The particle size D50 of the particles in the inner core layer-middle layer glue solution is 360 nm, and the viscosity of the inner core layer-middle layer glue solution is 420 cps; The particle size D50 of the core-shell structured binder particles is 450 nm, and the viscosity of the core-shell structured binder is 600 cps.
[0058] In some embodiments, the reaction temperature for preparing the inner core layer glue is 20-40°C, the reaction time is 3-8h, and the reaction pressure is 5-8Mpa; The reaction temperature for preparing the inner core layer-intermediate layer glue solution is 30-50°C, the reaction time is 8-10h, and the reaction pressure is 3-7Mpa; The reaction temperature for preparing the core-shell structure binder is 20-40° C., the reaction time is 5-8 hours, and the reaction pressure is 3-5 MPa.
[0059] Specifically, the reaction temperature for preparing the inner core layer glue solution is 30°C, the reaction time is 6h, and the reaction pressure is 7Mpa; The reaction temperature for preparing the inner core layer-intermediate layer glue solution is 50° C., the reaction time is 10 h, and the reaction pressure is 7 MPa; The reaction temperature for preparing the core-shell structure binder is 30° C., the reaction time is 8 h, and the reaction pressure is 5 MPa.
[0060] In another embodiment of the present invention, a current collector primer slurry is provided, comprising a second solvent, a conductive agent and the binder.
[0061] In some embodiments, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and carbon fibers; Taking the total mass of the current collector primer slurry as 100%, the mass percentage of the conductive agent is 50%-70%, and the mass percentage of the binder is 30%-50%.
[0062] In some embodiments, the current collector primer slurry further includes an auxiliary binder, and the auxiliary binder includes at least one of sodium carboxymethyl cellulose, polyvinylidene fluoride, a copolymer of vinylidene fluoride, and polytetrafluoroethylene.
[0063] In a specific embodiment, the conductive agent is selected from conductive carbon black and carbon nanotubes, and the auxiliary binder is selected from sodium carboxymethyl cellulose, wherein the negative electrode primer slurry is prepared within the mass ratio range of conductive carbon black: carbon nanotubes: sodium carboxymethyl cellulose: binder = (60-65): (3-5): (2-3.5): (26.5-28).
[0064] Specifically, the preparation of the current collector primer slurry includes the following operations: Dissolve sodium carboxymethyl cellulose to make glue, then add carbon nanotubes and stir to disperse, then add conductive carbon black to fully disperse, finally add binder, stir and disperse at high speed for 2 hours, stir and disperse evenly, scrape and measure the slurry fineness and viscosity, and if qualified, it can be discharged and coated; The solid content of the current collector primer slurry obtained after stirring is 12%-15%, the viscosity is 300-1000cps, and the fineness is less than 5μm.
[0065] In the preparation of the binder described in the present application, it is not necessary to add a dispersant and a wetting agent separately, and the dispersion of the conductive agent can be improved, and the ability of the current collector primer slurry to conduct electrons can be improved; and the binder can also improve the peel strength between the current collector primer slurry and the foil and reduce the contact internal resistance; by reducing the introduction of dispersants and wetting agents, the seepage of small molecules in the electrolyte can be reduced, and the high-temperature cycle and storage performance of the battery core can be improved; the inventors found in the early experimental verification that the use of the binder provided in the present application to prepare the current collector primer slurry can effectively improve the stability of the particle size of the current collector primer slurry. Compared with the current collector primer slurry prepared by the conventional formula, the particle size fineness is reduced by 1-1.5μm, and the viscosity stability fluctuates by 100cps; The present invention is further described below by way of examples.
[0066] Example 1 This embodiment is used to illustrate a binder, a binder preparation method and a negative electrode sheet disclosed in the present invention, and includes the following steps: Deionized water was added to a 50L autoclave, with the deionized water accounting for 50% of the volume of the autoclave. N2 was then introduced to replace the oxygen. Emulsifiers sodium dodecylbenzene sulfonate and disproportionated rosin acid potassium soap were added, with the emulsifier accounting for 2% of the total amount of the synthetic monomers. The mixture was then stirred at a linear speed of 7 m / s, and a certain amount of electrolyte potassium phosphate was added, and the mixture was stirred and dispersed evenly. The inner core layer monomers were added into the reaction kettle in a molar ratio of butadiene: styrene: 2-acrylamide: methacrylamide = 15:75:3:7, fully stirred and dispersed evenly, the pressure in the kettle was adjusted to 7Mpa and the temperature was adjusted to 30°C, and then an initiator was added to promote the copolymerization reaction of the inner core layer monomers styrene, butadiene, acrylamide, etc., and the reaction was carried out for 6 hours to obtain the inner core layer glue (particle size 120nm, viscosity 300cps); The inner core layer glue solution was transferred to an 80L high-pressure reactor, and a certain amount of emulsifier sodium dodecylbenzene sulfonate, disproportionated potassium rosin acid soap, deionized water and electrolyte potassium phosphate were added, and then the middle layer copolymer monomer was added according to the molar ratio of styrene: butadiene: ethyl acrylate: butyl acrylate: 2-ethylhexyl acrylate = 40: 45: 3: 8: 4, and the mixture was fully stirred and dispersed evenly. The temperature in the reactor was adjusted to 50°C and the pressure in the reactor was adjusted to 7Mpa. The initiator was added, and then the mixture was fully stirred at a linear speed of 8m / s. After reacting for 10 hours, when the conversion rate reached 80%, the inner core layer-middle layer glue solution (particle size 360nm, viscosity 420cps) was obtained; On the basis of the above-mentioned inner core layer-middle layer glue, a certain amount of emulsifier, deionized water, etc. are continued to be added, and then the mixture is fully stirred at a linear speed of 5 m / s, and then the outer shell layer copolymer monomer is added in a molar ratio of butadiene: 2-acrylamide-2-methylpropane sulfonic acid: trihydroxy polyoxypropylene ether: propenyl phenyl ether: maleic acid = 50:15:7:8:20, and then an initiator is added at 30°C and 5Mpa. After reacting for 8 hours, when the conversion rate reaches 95%, a core-shell structured adhesive (emulsion particle size 450nm, viscosity 600cps) is obtained. In the core-shell structured adhesive, the ratio of the copolymer monomers of the inner core layer, the middle layer and the outer shell layer is 30:60:10.
[0067] The current collector primer slurry with a solid content of 15% was prepared by stirring in the ratio of SP: CNT: CMC: binder = 65: 5: 2: 28, and then it was coated on the copper foil with a thickness of 3 μm by gravure coating, and baked and dried to obtain the negative electrode primer. The negative electrode slurry with a 5% silicon-carbon formula was coated on the above negative electrode primer, and then rolled and divided into strips to make pole pieces and assembled into battery cells.
[0068] Example 2 This embodiment is used to illustrate a binder, a binder preparation method and a negative electrode sheet disclosed in the present invention, and includes most of the operations in Example 1, except that: In the preparation of the inner core layer glue solution, the reaction monomers are put into the reactor in the ratio of butadiene: styrene: acrylamide: dimethylaminopropyl acrylamide = 15:75:4:6 to react and obtain the inner core layer glue solution; In the preparation of the inner core layer-middle layer glue solution, the reaction is carried out according to the molar ratio of styrene:butadiene:methyl acrylate:ethyl acrylate:pentaerythritol triacrylate = 45:40:5:6:4; The comonomers of the outer shell layer were reacted in a molar ratio of butadiene: 2-(styrenesulfonyl)acetic acid: propenylphenyl ether: 2-methyl-3-phenyl-2-propene-1-ol: itaconic acid = 50:15:12:8:15; The total monomer ratio of the inner layer: middle layer: outer layer of the core-shell structure adhesive is 30:50:20.
[0069] Example 3 This embodiment is used to illustrate a binder, a binder preparation method and a negative electrode sheet disclosed in the present invention, and includes most of the operations in Example 1, except that: In the preparation of the inner core layer glue solution, the reaction monomers are put into the reactor in the ratio of butadiene: styrene: 2-acrylamide: methacrylamide = 15:75:5:5 to react and obtain the inner core layer glue solution; In the preparation of the inner core layer-middle layer glue solution, the reaction is carried out according to the ratio of styrene:butadiene:methyl acrylate:2-ethylhexyl acrylate:methoxyethyl acrylate=45:40:4:5:6; The comonomers of the outer shell layer react in a ratio of butadiene: 2-acrylamide-2-methylpropanesulfonic acid: trihydroxy polyoxypropylene ether: propenyl phenyl ether: maleic acid = 50:15:10:10:15; The total monomer ratio of the inner layer: middle layer: outer layer of the core-shell structure adhesive is 30:40:50.
[0070] Comparative Example 1 This comparative example is used to compare and illustrate a binder, a binder preparation method and a negative electrode sheet disclosed in the present invention, and includes most of the operations in Example 1, except that: Conventional emulsion was used to synthesize SBR, wherein the ratio of butadiene to styrene in SBR was 30:70. Conventional ether wetting agent dodecylphenol polyoxyethylene ether was used. Conventional SBR and dispersant were placed in a conductive slurry and stirred and dispersed. The conductive slurry with a solid content of 15% was prepared by stirring at a ratio of SP: CNT: CMC: SBR: dispersant = 65: 5: 3: 26.5: 0.5.
[0071] Comparative Example 2 This comparative example is used to compare and illustrate a binder, a binder preparation method and a negative electrode sheet disclosed in the present invention, and includes most of the operations in Example 1, except that: The conventional emulsion was used to synthesize SBR, wherein the ratio of butadiene to styrene in SBR was 30:70, and the conventional alcohol ether wetting agent 2-amino-2-methyl-1-propanol was used. The conventional SBR and dispersant were placed in the conductive slurry and stirred and dispersed, wherein the conductive slurry with a solid content of 14% was prepared by stirring in the ratio of SP: CNT: CMC: SBR: dispersant = 65: 5: 3: 26.2: 0.8.
[0072] Comparative Example 3 This comparative example is used to compare and illustrate a binder, a binder preparation method and a negative electrode sheet disclosed in the present invention, and includes most of the operations in Example 1, except that: The copolymer monomers of the outer core layer of the binder do not include sulfonic acid monomers and alcohol ether monomers.
[0073] Performance Testing The following performance tests were performed on Examples 1-3 and Comparative Examples 1-3 prepared as above: 1. Slurry suspension stability test: The binder provided in the present application is prepared according to relevant proportions to obtain relevant slurry, and the changes in viscosity, fineness and solid content of the relevant slurry within 24 hours are tested.
[0074] 2. Appearance test of coated pole piece: The binder provided in this application was mixed with other components in the current collector primer slurry to prepare a conductive slurry, which was coated on a 6 μm copper foil. The thickness was controlled to be 3 μm after coating and the oven coating temperature settings for gravure coating were 80°C, 90°C, 110°C, 110°C, and 95°C. The coating interface was observed to see if there were pits, scratches, or pinholes.
[0075] 3. Internal resistance test of diaphragm after coating The copper foil base coated electrode after gravure coating is cut into small discs with a diameter of 1 cm, and then the diaphragm internal resistance of the small discs is tested using a diaphragm internal resistance meter.
[0076] 4. Peeling force test of the primer electrode after coating; The coated and rolled electrode was cut into 2cm*20cm strips, then attached to a steel plate and stretched at a speed of 5cm / min to obtain the tensile peeling force of the primer-coated electrode.
[0077] 5. Battery DC internal resistance DCR test The above copper foil primer was coated with negative electrode slurry to make corresponding electrode sheets, and then the manufactured battery cells were sent for testing of battery cell DCR. Under the temperature condition of 20°C, the battery cells were discharged at a discharge rate of 4C for 15s, and the discharge DCR of the battery cells at room temperature was compared.
[0078] 6. 60℃ cyclic expansion test The current collector primer slurry including the binder provided in the present application is applied to the surface of the negative electrode sheet to make a electrode sheet, and then the battery cell finally manufactured is sent for a 60°C cycle test, and the effect of the dispersant on the gas production is fed back by testing the thickness expansion of the battery cell; the above-mentioned battery cell is cycled at 1C / 1C for 800 weeks at 60°C to test the thickness expansion of the battery cell.
[0079] Fill in the test results obtained in the table below.
[0080] Table 1 It can be seen from the slurry suspension stability test results in Table 1 that the test results of Examples 1-3 are better than those of Comparative Examples 1-3 as a whole; among them, in Comparative Examples 1-2, the conventional SBR used, the slurry system to which a conventional dispersant is added, has a large increase in viscosity, particle flocculation and slurry sedimentation; in the process of preparing the binder in Comparative Example 3, the comonomers in the outer core layer do not include sulfonic acid monomers and alcohol ether monomers, the slurry stability is not good, and the fineness and solid content are significantly deteriorated.
[0081] Table 2 From the appearance test results of the coated electrodes in Table 2, it can be seen that the test results of Examples 1-3 are better than those of Comparative Examples 1-3 as a whole. Among them, the coating interfaces of Examples 1-3 have good leveling properties and the coating has no appearance abnormalities, while the coating interfaces of Comparative Examples 1-3 all have poor appearance problems such as pits and pinholes.
[0082] Table 3 From the diaphragm internal resistance test results in Table 3, it can be seen that the test results of Examples 1-3 are better than those of Comparative Examples 1-3 as a whole; among them, the diaphragm internal resistance of Examples 1-3 is significantly lower than that of Comparative Examples 1-2 with conventional formulas, and is also significantly lower than that of the binder in which the copolymer monomers in the outer core layer of Comparative Example 3 do not include sulfonic acid monomers and alcohol ether monomers; compared with Example 1 and Example 2 and Example 3, in the process of preparing the binder, Example 3 has the highest proportion of polymerized monomers in the outer core layer, followed by Example 2, and the internal resistance of Example 1 in the diaphragm internal resistance test result is the smallest, that is, within the scope of the present application, when the proportion of polymerized monomers in the outer core layer increases, the internal resistance of the diaphragm decreases accordingly.
[0083] Table 4 From the electrode peeling force test results in Table 4, it can be seen that the peeling strength of Examples 1-3 is better than that of Comparative Examples 1-3 as a whole; among them, Comparative Example 1-2 uses conventional SBR and has poor peeling force; Compared with Examples 1-3, although Comparative Example 3 includes the polymerized monomers in the inner core layer and the middle layer of the adhesive prepared in Examples 1-3, the outer shell layer does not use sulfonic acid monomers and alcohol ether monomers to modify the prepared adhesive, and its peeling force is also poor.
[0084] Table 5 From the battery DC internal resistance DCR test results in Table 5, it can be seen that the test results of Examples 1-3 are better than those of Comparative Examples 1-3; among them, by comparing Examples 1-3 and Comparative Examples 1-2, it can be clearly found that the DCR is significantly reduced by using the binder provided by the present application relative to the conventional SBR plus dispersant formula; by comparing Examples 1-3, it can be seen that the test result of Example 3 is the best, followed by Example 2, and Example 1 is the worst. The reason is that in Examples 1-3, in the process of preparing the binder, Example 3 has the highest proportion of the outer core layer polymerized monomers, that is, within the limit of the present application When the proportion of the polymerized monomer in the outer core layer increases, the DC internal resistance DCR of the battery decreases accordingly; among comparative examples 1-3, the DCR of comparative example 3 is the lowest, followed by comparative example 2, and the DCR of comparative example 1 is the worst. Among them, comparative example 2 has an additional dispersant added, which can better disperse the conductive agent, so the DC internal resistance DCR is lower than that of comparative example 1; the surface of comparative example 3 is modified with acrylic esters, etc., and has a better affinity for the electrolyte, which can well improve the diffusion of lithium ions in the electrolyte. Therefore, the DCR of comparative example 3 is reduced to a certain extent compared with comparative examples 1 and 2. Table 6 From the battery cycle expansion performance test in Table 6, it can be seen that the test results of Examples 1-3 are better than those of Comparative Examples 1-3; among them, compared with Comparative Examples 1-3, it can be clearly found that the SBR used in Comparative Example 1-2 is directly added with a dispersant in its formula system, and the dispersant is dissolved in the electrolyte and oxidized under high voltage to produce gas. Secondly, the dissolution of the dispersant will deteriorate the stability of the electrode structure, thereby causing the high-temperature cycle expansion of the battery cell to deteriorate significantly. In addition, the proportion of dispersant in Comparative Example 2 is slightly higher than that in Comparative Example 1, and its high-temperature cycle performance is slightly worse than that of Comparative Example 1; the process of preparing the adhesive in Comparative Example 3 does not modify the sulfonic acid monomer and the alcohol ether monomer, and there is also a problem of deteriorated cycle expansion.
[0085] By comparing the test results of the batteries prepared in Table 1 and Table 6, it can be seen that the use of the binder provided in the present application is conducive to dispersing the conductive slurry. The dispersed slurry is more stable, the viscosity fluctuation is low, the interface consistency after coating is good, the peel strength is improved, and the internal resistance of the membrane is significantly improved. In addition, the binder provided in the present application does not require the addition of additional dispersants and wetting agents, which can reduce the process difficulty and reduce the high-temperature deterioration caused by the dissolution of small molecule organic matter in the electrolyte.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A binder, characterized in that: The binder is a core-shell structure, including a core layer, an intermediate layer and an outer shell layer, wherein the intermediate layer is arranged between the core layer and the outer shell layer, and the comonomer of the core layer includes olefin monomers, aromatic vinyl monomers and unsaturated amide monomers; The comonomers of the intermediate layer include olefin monomers, aromatic vinyl monomers and unsaturated ester monomers; The comonomers of the outer shell layer include olefin monomers, sulfonic acid monomers, alcohol ether monomers and acrylic acid monomers.
2. The adhesive according to claim 1, characterized in that: The molar ratio of the comonomers of the inner core layer, the middle layer and the outer shell layer is (20-30): (40-60): (10-40).
3. The adhesive according to claim 1, characterized in that: The molar ratio of olefin monomers, aromatic vinyl monomers and unsaturated amide monomers in the inner core layer is (10-30): (64-84): (5-7).
4. The adhesive according to claim 1, characterized in that: The molar ratio of the olefin monomer, the aromatic vinyl monomer and the unsaturated ester monomer in the intermediate layer is (30-40): (40-50): (10-30).
5. The adhesive according to claim 1, characterized in that: The molar ratio of olefin monomers, sulfonic acid monomers, alcohol ether monomers and acrylic acid monomers in the outer shell layer is (30-40): (10-20): (20-30): (20-30).
6. The adhesive according to claim 1, characterized in that: The aggregation structure of the kernel layer is: , Wherein, x is the degree of polymerization of the olefin monomer, y is the degree of polymerization of the aromatic vinyl monomer, and z is the degree of polymerization of the unsaturated amide monomer, x:y:z = (10-30): (64-84): (5-7).
7. The adhesive according to claim 1, characterized in that: The polymer structure of the intermediate layer is: , Wherein, m is the degree of polymerization of the olefin monomer, n is the degree of polymerization of the aromatic vinyl monomer, and p is the degree of polymerization of the unsaturated ester monomer, m:n:p = (30-40): (40-50): (10-30).
8. The adhesive according to claim 1, characterized in that: The polymeric structure of the outer shell layer is: , Among them, a is the degree of polymerization of olefin monomers, b is the degree of polymerization of sulfonic acid monomers, c is the degree of polymerization of alcohol ether monomers, and d is the degree of polymerization of acrylic acid monomers, a:b:c:d=(30-40):(10-20):(20-30):(20-30).
9. The adhesive according to claim 1, characterized in that: The olefin monomers include one or more of butadiene and isoprene; and / or, The aromatic vinyl monomer includes one or more of styrene, α-methylstyrene, and vinyltoluene; and / or, The unsaturated amide monomers include one or more of acrylamide, 2-acrylamide, methacrylamide, dimethylaminopropyl acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid; and / or, The unsaturated ester monomers include one or more of methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methoxyethyl acrylate, and pentaerythritol triacrylate; and / or, The sulfonic acid monomers include one or more of 2-acrylamide-2-methylpropanesulfonic acid, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 2-(styrenesulfonyl)acetic acid, and allyl methylthiosulfonate; and / or, The alcohol ether monomers include one or more of trihydroxy polyoxypropylene ether, propenyl phenyl ether, 2-methyl-3-phenyl-2-propene-1-ol, and 1-(furan-2-yl)but-3-ene-1-ol; and / or, The acrylic monomer includes one or more of acrylic acid, maleic acid and itaconic acid.
10. A binder slurry, characterized in that: The binder slurry comprises a first solvent and the binder according to any one of claims 1 to 9, wherein the solid content of the binder is 35% to 40%.
11. The binder slurry according to claim 10, characterized in that: The binder slurry also includes an emulsifier, an initiator and a stopper; Taking the total mass of the binder slurry as 100%, the mass percentage of the emulsifier is 1%-2%, the mass percentage of the initiator is 0.4%-0.6%, and the mass percentage of the terminator is 1%-2%.
12. The binder slurry according to claim 11, characterized in that: The emulsifier includes one or more of alkyl sulfonates such as sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate, and sodium dodecylbenzene sulfonate; and / or The initiator is a redox initiator, and the redox initiator includes one or more of dicumyl peroxide, azobisisobutyronitrile and ferrous sulfate; and / or The stopper includes one or more of 2-mercaptoethanol, 3-mercaptopropionic acid, 4-mercaptobutyric acid and 6-mercaptohexanoic acid.
13. The method for preparing a binder slurry according to claim 10, characterized in that: The following operations are included: S1: taking the comonomer of the inner core layer and adding it into the emulsion, mixing it evenly, and obtaining the inner core layer glue after polymerization reaction; S2: taking the comonomer of the middle layer and adding it into the inner core layer glue solution, mixing them evenly, and obtaining the inner core layer-middle layer glue solution after polymerization reaction; S3: Take the comonomer of the outer shell layer and add it into the inner core layer-middle layer glue solution, mix well, and obtain the adhesive slurry after polymerization reaction.
14. The method for preparing a binder slurry according to claim 13, characterized in that: The particle size D50 of the inner core layer glue is greater than 100 nm, and the viscosity of the inner core layer glue is greater than 100 cps; The particle size D50 of the inner core layer-middle layer glue solution is greater than 350 nm, and the viscosity of the inner core layer-middle layer glue solution is greater than 300 cps; The particle size D50 of the binder in the binder slurry is less than 500 nm, and the viscosity of the binder slurry is greater than or equal to 600 cps.
15. The method for preparing a binder slurry according to claim 13, characterized in that: The reaction temperature for preparing the inner core glue is 20-40°C, the reaction time is 3-8h, and the reaction pressure is 5-8Mpa; The reaction temperature for preparing the inner core layer-intermediate layer glue solution is 30-50°C, the reaction time is 8-10h, and the reaction pressure is 3-7Mpa; The reaction temperature for preparing the core-shell structure binder is 20-40° C., the reaction time is 5-8 hours, and the reaction pressure is 3-5 MPa.
16. A current collector primer slurry, characterized in that: The invention comprises a second solvent, a conductive agent and the binder according to any one of claims 1 to 9.
17. The current collector primer slurry according to claim 16, characterized in that: The conductive agent includes one or more of conductive carbon black, carbon nanotubes, graphene, and carbon fibers; Taking the total mass of the current collector primer slurry as 100%, the mass percentage of the conductive agent is 50%-70%, and the mass percentage of the binder is 30%-50%.
18. A negative electrode sheet, characterized in that: The invention comprises a current collector, an undercoat layer and a negative electrode active material layer, wherein the undercoat layer is located between the current collector and the negative electrode active material layer; The primer layer comprises the binder according to any one of claims 1 to 9, or the primer layer is obtained by coating and curing the current collector primer slurry according to claim 16 or 17.
Citation Information
Cited By
Negative electrode binder, electrode plate and battery
CN121343519A
Negative electrode binder, preparation method of negative electrode binder, negative electrode plate and battery
CN121687954A